Fracture toughness of railway track material using finite element analysis - Mohd Nurul Akmal, Mohd Yusof (2010)
Railway track are used as way for carrying cargo or passengers from one place to another place. Nowadays, Malaysia still using the old railway line and accidents can happen at any time due to several factors, namely high density load of railroad rails, cracks due to vibration and friction wheel. Therefore, in this project the analysis is to prevent and predict the occurrence of harm or injury to passengers, and goods. The objective of this project is to determine the value of fracture toughness of railway track material using analytical solution. Finite element analysis is used to find the value of stress that has been used in analytical equation. The design of the model specimen drawn by Solidworks software and then imported into the Patran software to key in data such as load, material, element, and properties. Then, Nastran software is used as a solver and decision analysis model will be produced when the specimen is successful simulated. Comparisons are made between the simulation using finite element analysis and previous research. The result shows that the fracture toughness decreasing when the thickness is increasing. The average value of fracture toughness found was 39.02 MPa.√m. It is said to be plane strain fracture toughness.